A Case of Generalized Tooth Wear caused by Bruxism and its Rehabilitation (City Dental College Journal, 2018)
Bruxism may lead to dental problem such as tooth wear, fracture,  crack of tooth, muscles of mastication discomfort, temporomandibular  joint (TMJ) dysfunction syndrome and periodontal signs  such as gingival recession and tooth mobility. This article presents a  case report in which bruxism caused severe tooth wear that lead to  great muscular discomfort with TMJ pain. The initial treatment  approach was the installation of an inter-occlusal acrylic device in  centric relation of occlusion for re-establishment of the occlusal  stability. Vertical dimension of occlusion, anterior guides and return  of normal muscle activity were observed within 3 months. After  subsiding primary symptoms, oral rehabilitation therapy was  approached by means of metal bond ceramic restoration and new  inter-occlusal device was provided for protection of restoration.  Satisfactory aesthetics, improved function, occlusal stability were  obtained after oral rehabilitation therapy. No specific trouble occurred  during 1 year follow up period. DOI: http://dx.doi.org/10.3329/cdcj.v10i1.13747 City Dent. Coll. J Volume-10, Number-1, January-2013